Food access, local foods, and community health. Issue 5 (20th October 2017) - Deller, Steven; Canto, Amber; Brown, Laura
Abstract: In this analysis, we look for patterns in the relationship between food access, local foods, and community health at the US county level. We take an ecological approach using 2012 Census of Agriculture and County Health Rankings & Roadmaps data collected by the University of Wisconsin Population Health Institute. We address a simple question: is access to local foods activity associated with public health? Results generally support the central premise, but the results are weak depending on the metrics of health and local foods activity chosen. In the end, we concluded that local foods are likely demand driven, and the mere presence of local foods activity is not sufficient to result in healthier community outcomes.